Marketsforthecommercializationofeducationalhealthservicesofferedby Cuba - Carreño Cuador, Jenry (Horizonte Sanitario, 2023)
Objective: Characterize the markets for educational health services offered by Cuba.Material and Method: Study of technological development, using qualitative and quantitative techniques. Based on the bibliographic review, the dimensions in which the variables were grouped, their operationalization, scale, indicator or index were established. Questionnaires were constructed and validated to obtain the information, which was summarized in frequency, percentage, mean, standard deviation, and range. To measure the coincidence between the observers, the Cohen's Kappa Index was used, the confidence interval for Kappa was calculated, the standard error was estimated and it was interpreted using the scale proposed by Landis and Koch.Results: A list of countries was obtained as current and potential markets, in which there is a coincidence by the key informants consulted, supported by statistical tests. The countries identified as current and potential markets have very similar characteristics; They only differ in the variables: associations, unions or groups in the health sector that have declared resistance or opposition to commercial health relations with Cuba and difficulties in purchasing power to access educational services personally or for their family.Conclusions: The information obtained, limited to the countries that currently demand or have requested educational services, guides to encourage the current market, concentrating resources on maintaining them. The elaborated methodology allows new studies to be carried out in greater depth to identify potential markets and their segmentation. Set guidelines for your employment in the public sector internationally.Keywords: Market; Offer; Services; educational; Health.